The effect of antineoplastic drugs in a male spontaneous mammary tumor model - Shishido, Stephanie N.; Faulkner, Emma B.; Beck, Amanda; Nguyen, Thu A. (My University, 2013)
Male breast cancer is a rare disease. The limited number of clinical cases has led to the primary treatments for men being derived from female breast cancer studies. Here the transgenic strain FVB/N-Tg(MMTV-PyVT)634Mul/J (also known as PyVT) was used as a model system for measuring tumor burden and drug sensitivity of the antineoplastic drugs tamoxifen, cisplatin, and paclitaxel on tumorigenesis at an early stage of mammary carcinoma development in a male mouse model. Cisplatin treatment significantly reduced tumor volume, while paclitaxel and tamoxifen did not attenuate tumor growth. Cisplatin treatment was shown to induce apoptosis, grossly observed by reduced tumor formation, through reduced Bcl-2 and survivin protein expression levels with an increase in caspase 3 expression compared to control tumors. Tamoxifen treatment significantly altered the hormone receptor expression levels of the tumor, while additionally upregulating Bcl-2 and Cyclin D1. This suggests an importance in hormonal signaling in male breast cancer pathogenesis. The results of this study provide valuable information toward the better understanding of male breast cancer and may help guide treatment decisions.
Keywords: Breast cancer; Male breast cancer; Antineoplastic drugs